Inpatient care cost, duration, and acute complications associated with BMI in children and adults hospitalized for COVID‐19. Issue 10 (7th September 2022) - Kompaniyets, Lyudmyla; Goodman, Alyson B.; Wiltz, Jennifer L.; Shrestha, Sundar S.; Grosse, Scott D.; Boehmer, Tegan K.; Blanck, Heidi M.
Abstract: Objective: This study aimed to assess the association of BMI with inpatient care cost, duration, and acute complications among patients hospitalized for COVID‐19 at 273 US hospitals. Methods: Children (aged 2–17 years) and adults (aged ≥18 years) hospitalized for COVID‐19 during March 2020–July 2021 and with measured BMI in a large electronic administrative health care database were included. Generalized linear models were used to assess the association of BMI categories with the cost and duration of inpatient care. Results: Among 108, 986 adults and 409 children hospitalized for COVID‐19, obesity prevalence was 53.4% and 45.0%, respectively. Among adults, overweight and obesity were associated with higher cost of care, and obesity was associated with longer hospital stays. Children with severe obesity had higher cost of care but not significantly longer hospital stays, compared with those with healthy weight. Children with severe obesity were 3.7 times (95% CI: 1.4–9.5) as likely to have invasive mechanical ventilation and 62% more likely to have an acute complication (95% CI: 39%–90%), compared with children with healthy weight. Conclusions: These findings show that patients with a high BMI experience significant health care burden during inpatient COVID‐19 care.